1. The formula used to solve for the slope of a line is:
slope (m) = (y2 - y1) / (x2 - x1)
2. The correct set up of this problem is:
(8 - y) / (4 - (-6))
Note: (-6) - (-6) simplifies to (-6) + 6 = 0
3. When solving this problem, in order to get the variable y out of the numerator, you must multiply both sides of the equation by (4 - (-6)) or (4 + 6), which equals 10.
4. The correct value for the missing y is -17.
Here's the full solution:
(8 - y) / 10 = 5/2
Multiply both sides by 10:
8 - y = 25/2
To isolate y, subtract 8 from both sides:
-y = 25/2 - 8
Simplify and find a common denominator:
-y = 25/2 - 16/2
-y = 9/2
Multiply both sides by -1 to solve for y:
y = -9/2
y = -4.5
the pair of points (-6,y) and (4,8) lie on a line with a slope of 5/2.
1.the formula used to solve for the slope of a line is
2.the correct set up of this problem is 8-y/4-(-6)=
3.when solving this problem, in order to get the variable y out of the numerator you must _
4.the correct value for the missing y is _
y2-y1/x2-x1, -17, x2-x1/y2-y1, cross multiply, -5/2, y2+y1/x2+x1, -4, 2/5, combine like terms, 4, 5/2, distrubitive property
5 answers
i dont think that is correct?
Apologies for the error in the previous response. Let's solve it correctly:
Given points:
Point 1: (-6, y)
Point 2: (4, 8)
Using the formula for slope:
m = (y2 - y1) / (x2 - x1)
Substituting the values:
5/2 = (8 - y) / (4 - (-6))
5/2 = (8 - y) / 10
To get rid of the fraction, we can cross multiply:
2(8 - y) = 5(10)
16 - 2y = 50
-2y = 50 - 16
-2y = 34
Divide by -2:
y = 34 / -2
y = -17
The correct value for the missing y is -17.
Given points:
Point 1: (-6, y)
Point 2: (4, 8)
Using the formula for slope:
m = (y2 - y1) / (x2 - x1)
Substituting the values:
5/2 = (8 - y) / (4 - (-6))
5/2 = (8 - y) / 10
To get rid of the fraction, we can cross multiply:
2(8 - y) = 5(10)
16 - 2y = 50
-2y = 50 - 16
-2y = 34
Divide by -2:
y = 34 / -2
y = -17
The correct value for the missing y is -17.
the correct set up of this problem is 8-y/4-(-6)=
Apologies for the confusion.
The correct set up of the problem is:
(8 - y) / (4 - (-6)) =
Simplifying the expression:
(8 - y) / (4 + 6) =
(8 - y) / 10
To get the variable y out of the numerator, you can multiply both sides of the equation by 10:
10 * (8 - y) / 10 = 10/10
Simplifying further:
8 - y = 1
Now, to solve for y, subtract 8 from both sides:
- y = 1 - 8
- y = -7
The correct value for the missing y is -7.
The correct set up of the problem is:
(8 - y) / (4 - (-6)) =
Simplifying the expression:
(8 - y) / (4 + 6) =
(8 - y) / 10
To get the variable y out of the numerator, you can multiply both sides of the equation by 10:
10 * (8 - y) / 10 = 10/10
Simplifying further:
8 - y = 1
Now, to solve for y, subtract 8 from both sides:
- y = 1 - 8
- y = -7
The correct value for the missing y is -7.